The Rule Of Law Corrupted By Law Enforcers: a Study Of Police Misconduct - Saida Flora, Henny; Suhendar, Suhendar; Fitri Hertini, Mega; Itasari, Endah Rantau; Erwin, Erwin (Universitas Ekasakti, 2024)
The purpose of this study was to study and know the provisions of the Police Code of Ethical Principles that are the basis for the performance of duty, to study and know the responsibility of the police for violating the Code of Ethical Principles, and to know the responsibility for the violation of the Code of Ethical Principles. According to the provisions of the Regulation of the Chief of the National Police of Indonesia No. 14 of 2011 on the Code of Ethical Principles of the National Police of Indonesia, Article 1 regarding the definition of KEPP, viz.